2010
DOI: 10.3109/08977194.2010.484423
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and BMP-6 enhance bone formation mediated by cloned mouse osteoprogenitor cells

Abstract: New strategies such as combined utilization of growth factors may provide a better treatment for difficult fractures. We have demonstrated enhanced angiogenesis and osteogenesis through the actions of vascular endothelial growth factor (VEGF) and bone morphogenetic protein-6 (BMP-6) on the osteogenic differentiation of a cloned mouse osteoprogenitor cell in vitro and ectopic bone formation in vivo. Human VEGF and BMP-6 genes expressed together produced a significant increase in alkaline phosphatase activity, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 42 publications
4
47
0
Order By: Relevance
“…Likewise, combination therapy of BMP-2 and BMP-7 transduction of cells implanted into a cranial defect enhanced healing (Koh et al, 2008). Combination therapy of VEGF and BMP-6 transduction of osteoprogenitor cells has also shown preliminary promising results for future fracture repair studies (Cui et al, 2010). In addition to BMPs, one study found that cells transduced with IGF-I injected post-fracture resulted in accelerated progression toward complete fracture healing as measured by percent of mineralized callus and mineralized matrix compared to controls (Shen et al, 2002).…”
Section: Cell Vectorsmentioning
confidence: 97%
“…Likewise, combination therapy of BMP-2 and BMP-7 transduction of cells implanted into a cranial defect enhanced healing (Koh et al, 2008). Combination therapy of VEGF and BMP-6 transduction of osteoprogenitor cells has also shown preliminary promising results for future fracture repair studies (Cui et al, 2010). In addition to BMPs, one study found that cells transduced with IGF-I injected post-fracture resulted in accelerated progression toward complete fracture healing as measured by percent of mineralized callus and mineralized matrix compared to controls (Shen et al, 2002).…”
Section: Cell Vectorsmentioning
confidence: 97%
“…Physical scaffold parameters, such [2] and proliferation of pre-osteoblastic cells [3] A late-stage osteogenic differentiation marker, induced by Wnt/β-catenin signaling […”
Section: Porous Scaffoldsmentioning
confidence: 99%
“…Throughout the processes of osteoblast differentiation, matrix mineralization, tissue repair and bone regeneration, the expression and levels of OPN and VEGF vary (Table 1) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Skeletal Healing and Remodelingmentioning
confidence: 99%
“…Combined use of VEGF and BMP-2 [19,24,34,35,37,40] and BMP-4 [20,25,36] showed synergistic effects in osteogenesis. It has been shown that combined use of VEGF with one of the most potent BMPs, BMP-6 [23,26], enhances osteogenesis and angiogenesis of mouse bone marrow stem cells in vitro and in vivo [8], however, the effectiveness of this therapy for ON has not been determined.…”
Section: Questions/hypothesesmentioning
confidence: 99%
“…It has been shown that VEGF enhances BMP-6-induced osteogenesis of mouse stem cells in vitro and in vivo, however, the effectiveness of this therapy for ON has not been determined [8]. If it is effective in treating ON induced in an animal model, then the composite graft material can be used to treat the human form of the disease.…”
Section: Next Stepsmentioning
confidence: 99%